Minocycline intra-bacterial pharmacokinetic hysteresis as a basis for pharmacologic memory and a backbone for once-a-week pan-tuberculosis therapy - Deshpande, Devyani; Srivastava, Shashikant; Pasipanodya, Jotam Garaimunashe; Gumbo, Tawanda (Frontiers in Pharmacology, 2022)
Background: There is need for shorter duration regimens for the treatment of tuberculosis, that can treat patients regardless of multidrug resistance status (pan-tuberculosis). Methods: We combined minocycline with tedizolid, moxifloxacin, and rifampin, in the hollow fiber system model of tuberculosis and mimicked each drugs’ intrapulmonary pharmacokinetics for 28 days. Minocycline-tedizolid was administered either as a once-a-week or a daily regimen. In order to explore a possible explanation for effectiveness of the once-a-week regimen, we measured systemic and intra-bacterial minocycline pharmacokinetics. Standard daily therapy (rifampin, isoniazid, pyrazinamide) was the comparator. We then calculated γf or kill slopes for each regimen and ranked the regimens by time-to-extinction predicted in patients. Results: The steepest γf and shortest time-to-extinction of entire bacterial population was with daily minocycline-rifampin combination. There was no difference in γf between the minocycline-tedizolid once-a-week versus the daily therapy (p = 0.85). Standard therapy was predicted to cure 88% of patients, while minocycline-rifampin would cure 98% of patients. Minocycline concentrations fell below minimum inhibitory concentration after 2 days of once-weekly dosing schedule. The shape of minocycline intra-bacterial concentration-time curve differed from the extracellular pharmacokinetic system and lagged by several days, consistent with system hysteresis. Hysteresis explained the persistent microbial killing after hollow fiber system model of tuberculosis concentrations dropped below the minimum inhibitory concentration. Conclusion: Minocycline could form a backbone of a shorter duration once-a-week pan-tuberculosis regimen. We propose a new concept of post-antibiotic microbial killing, distinct from post-antibiotic effect. We propose system hysteresis as the basis for the novel concept of pharmacologic memory, which allows intermittent dosing.